Parenting 101 basic skills for raising confident children - Dimoff, Diane (London : Meridian Education Corporation, 2011)
Practical advice on building a strong parent-child relationship, teaching and reinforcing desirable behavior, creating an environment that stimulates intellect and confidence, developing a routine that offer reassurance and stability, and working through parental conflict constructively. Concise dramatizations that highlight problems and solutions are combined with helpful commentary from educators, counselors, and psychologists
Executive producers, Brad Kloza, Diana Sole Walko ; videographer/editor, Wesley Poole; graphics and production assistant, Ward Hiney.
Host, Sandra Cole
DVD format
Subtitle available in English
Keywords: Parenting; Child rearing; Personality development